2006
DOI: 10.1074/jbc.m511572200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Segments of the Mouse Transferrin Receptor 1 Required for Mouse Mammary Tumor Virus Infection

Abstract: Most enveloped viruses enter cells through binding of virion surface envelope proteins to receptors found on the plasma membrane of the cell. The beta retrovirus mouse mammary tumor virus (MMTV) uses transferrin receptor 1 (TfR1) to enter cells in a pHdependent mechanism, probably co-trafficking with TfR1 to an acidic compartment where virus entry occurs. We have shown here that, although mouse and rat TfR1 function as entry receptors, cat, dog, hamster, or human TfR1s do not support MMTV infection. We also de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 45 publications
0
36
0
Order By: Relevance
“…It has previously been reported that mouse mammary tumor virus (MMTV) uses TfR1 for entry and, in an opposite pattern from what we observe for the arenaviruses, is able to use the murine but not the human version of this molecule (34). Through the use of human/murine chimeras, the residues responsible for this species difference in MMTV utilization have been mapped to two regions that are spatially close on the surface of TfR1, at the outer edge of the TfR1 homodimer, in a region that is distinct from the binding sites for either of its natural ligands, transferrin or the hereditary hematochromatosis protein, HFE (34). Since it has also been demonstrated that soluble transferrin does not compete with MACV GP vectors for entry into human cells (25), we asked if the clade B GPs could be binding to a region of hTFR1 similar to the one MMTV uses on mTfR1.…”
Section: Resultsmentioning
confidence: 44%
See 1 more Smart Citation
“…It has previously been reported that mouse mammary tumor virus (MMTV) uses TfR1 for entry and, in an opposite pattern from what we observe for the arenaviruses, is able to use the murine but not the human version of this molecule (34). Through the use of human/murine chimeras, the residues responsible for this species difference in MMTV utilization have been mapped to two regions that are spatially close on the surface of TfR1, at the outer edge of the TfR1 homodimer, in a region that is distinct from the binding sites for either of its natural ligands, transferrin or the hereditary hematochromatosis protein, HFE (34). Since it has also been demonstrated that soluble transferrin does not compete with MACV GP vectors for entry into human cells (25), we asked if the clade B GPs could be binding to a region of hTFR1 similar to the one MMTV uses on mTfR1.…”
Section: Resultsmentioning
confidence: 44%
“…We analyzed the ability of the vectors to enter CHO-K1 cells transfected with a panel of reciprocal chimeras between hTfR1 and mTfR1 (Fig. 7A), with chimeras 3 to 5 and 16 containing substitutions in hTfR1 of the murine sequences necessary to confer full MMTV entry (34). As controls, we used VSV-G and TCRV GP vectors, neither of which is affected by the expression of either hTfR1 or mTfR1 in CHO-K1 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Beta-type ENVs are known to have restricted species tropism based on receptor usage; however, the range of cell types tested has been limited to those in which specific retroviruses can replicate (19,(22)(23)(24)(25)(26). Since the VSV core can replicate in all eukaryotic cells in culture, VSV-HERVK provides a unique reagent to interrogate more broadly the ability of HERV-K ENV to mediate entry into those cells.…”
Section: Resultsmentioning
confidence: 99%
“…MMTV uses the transferrin receptor of certain species of mice and rats (19,(22)(23)(24). JSRV uses Hyal2 from a variety of mammals, but not rodents (25), whereas ENTV uses only Hyal2 of ovine cells (25,26).…”
mentioning
confidence: 99%
“…2A) for their ability to bind MACV GP1⌬-Fc and support MACV, JUNV, and GTOV GP-mediated entry. Chimeras 1-6 have been previously described (42). All receptor chimeras were expressed on the cell surface to similar levels as determined by flow cytometry (Fig.…”
Section: Localization Of the Arenaviral Gp1-binding Determinants On Hmentioning
confidence: 99%